Low cement/fly ash blends for modification of Crushed Rock Base material - Rezagholilou, Ali; Ganjavi, B.; Nikraz, Hamid (Chinese Society of Pavement Engineering, 2018)
Crushed Rock Base (CRB) material sometimes needs to be modified typically due to the moisture susceptibility. Resilient modulus is the dominant design parameter of unbound materials and should be high enough to avoid distress or failure of a pavement. In Western Australia (WA), some modification methods such as dry-back or Hydrated Cement Treated Crushed Rock Base (HCTCRB) have been implemented in trial sections of pavements. But they could not provide the desired performances by poor drainability or widely-spaced open cracks in surface of thin bituminous pavements. As such, this paper attempts to review the challenges of each method and show how design requirements can be provided by another option so-called low cement/fly ash blends even in saturated conditions. This method covers the deficiencies of two previous methods in terms of cracking or moisture susceptibility as observed in limited field tests. Series of laboratory tests including uniaxial compression strength, resilient modulus, tube suction and shrinkage tests are undertaken to explore the key features of this modification method. Typical results indicated that resilient modulus improved two times while strength, shrinkage and capillary rise of this material are in the acceptable level.